2004
DOI: 10.1523/jneurosci.1476-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Semaphorin3A-Induced Facilitation of Axonal Transport and Local Activation of a Translation Initiation Factor Eukaryotic Translation Initiation Factor 4E

Abstract: An impressive body of evidence has been accumulated indicating that local protein synthesis is implicated in navigation of neurite extension induced by guidance cues, such as semaphorin3A (Sema3A). We found previously that a Src type tyrosine kinase Fyn and cyclin-dependent kinase 5 (Cdk5) mediate Sema3A-signaling. We also showed that Sema3A elicits axonal transport through neuropilin-1, a receptor for Sema3A, located at the growth cones. Here, we investigate the relationship between Sema3A-induced local signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 44 publications
3
67
0
Order By: Relevance
“…If the staining reflects the former case, it raises the possibility that the tyrosine phosphorylation may be involved in the regulation of axonal transport. In fact, Sema3A facilitates axonal transport, and this facilitation is blocked by a tyrosine kinase inhibitor and is attenuated in fyndeficient mouse DRG (25).…”
Section: Tyrosine Phosphorylation Site Of Crmp2 Is Tyrmentioning
confidence: 99%
“…If the staining reflects the former case, it raises the possibility that the tyrosine phosphorylation may be involved in the regulation of axonal transport. In fact, Sema3A facilitates axonal transport, and this facilitation is blocked by a tyrosine kinase inhibitor and is attenuated in fyndeficient mouse DRG (25).…”
Section: Tyrosine Phosphorylation Site Of Crmp2 Is Tyrmentioning
confidence: 99%
“…That the required proteins, in response to physiological signals, could be translated and folded in such a short period of time is not surprising. For instance, previous work (Li et al, 2004) has shown that such a time course is plausible, because semaphorin 3A, a secreted guidance cue for growth cones, can enhance the level of phosphorylated eukaryotic translation initiation factor 4E within 5 min of its application to cultured cells.…”
Section: Possible Role Of Local Axonal Translationmentioning
confidence: 99%
“…Semaphorin3A (Sema3A) repulses axons through the coreceptor protein neuropilin-1 and plexin-As (Takahashi et al, 1999;Tamagnone et al, 1999). Sema3A functions not only as a chemorepulsive cue but also in endocytosis, facilitation of axonal transport, and spine development, and as a chemoattractive cue (Nakamura et al, 2000;Polleux et al, 2000;Goshima et al, 2002;Huber et al, 2003;Li et al, 2004;Morita et al, 2006) through the Fyn-cyclin-dependent kinase 5 (Cdk5) cascade Li et al, 2004;Morita et al, 2006). Although, how Sema3A regulates the cytoskeleton remains obscure, several intracellular molecules have been implicated as their downstream molecules.…”
Section: Introductionmentioning
confidence: 99%